Relationship Between Pathologic T1 Categories and Pathologic Factors Affecting Prognosis in Pulmonary Adenocarcinoma - Hironori Ninomiya, MD, PhD; Kentaro Inamura, MD, PhD; Mingyon Mun, MD, PhD; Makoto Nishio, MD, PhD; Yuichi Ishikawa, MD, PhD (JTO Clinical and Research Reports, 2022)
Introduction: The eight TNM classification of lung tumors provides a more precise prediction of prognosis than previous classification systems, especially in T1 tumors, the invasion size of which are less than or equal to 3 cm. T1 is divided into T1a (6–10 mm), T1b (11–20 mm), and T1c (21–30 mm), but the relationship between pathologic T (pT)1 categories and other pathologic factors has not been thoroughly evaluated. Methods: Surgically resected pulmonary adenocarcinomas (N = 551) were extracted on the basis of computed tomography-based tumor size measurements, including 302 pT1a to c cases (pT1a: n = 98, pT1b: n = 156, and pT1c: n = 48). Pathologic factors, including a minor component of micropapillary or solid subtype, were analyzed by new T categories. Recurrence-free and disease-specific survivals (DSSs) were evaluated using univariable and multivariable analyses and Cox proportional hazards models. Results: Lymphatic invasion, vascular invasion, and nodal metastasis increased remarkably from pT1a to pT1c, step-wisely. Visceral pleural invasion was elevated from 7% (6–10 mm) to 33% (21–30 mm) along with an increase in invasion size. Recurrence-free survival (RFS) and DSS relevantly deteriorated from the group of pathologic stages 0, IA1, and IA2 to the group IA3 and IB. Multivariable analysis revealed that lymph node metastasis and solid components were independent prognostic factors for both RFS and DSS in pT1a to c cases. Conclusions: The new TNM classification precisely predicts prognosis. Tumor invasion size is closely associated with lymphatic and vascular invasion, nodal metastasis, and visceral pleural invasion. As a minor component, solid subtype was a potent adverse prognostic factor affecting both RFS and DSS after surgery in T1 categories.